Proceedings of the 9th Annual International Conference on Mobile Computing and Networking 2003
DOI: 10.1145/938985.939008
|View full text |Cite
|
Sign up to set email alerts
|

Towards realistic mobility models for mobile ad hoc networks

Abstract: One of the most important methods for evaluating the characteristics of ad hoc networking protocols is through the use of simulation. Simulation provides researchers with a number of significant benefits, including repeatable scenarios, isolation of parameters, and exploration of a variety of metrics. The topology and movement of the nodes in the simulation are key factors in the performance of the network protocol under study. Once the nodes have been initially distributed, the mobility model dictates the mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
202
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 411 publications
(208 citation statements)
references
References 17 publications
1
202
0
3
Order By: Relevance
“…Exponentially distributed destination selection: In our earlier model [19], we indicated that a node selects a destination randomly and then moves to that point by computing the shortest path. This selection method follows a uniform distribution, i.e., the probability with which a node selects a destination is independent of its distance to the destination.…”
Section: Mobility Variationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Exponentially distributed destination selection: In our earlier model [19], we indicated that a node selects a destination randomly and then moves to that point by computing the shortest path. This selection method follows a uniform distribution, i.e., the probability with which a node selects a destination is independent of its distance to the destination.…”
Section: Mobility Variationsmentioning
confidence: 99%
“…In our previous work [19], we assumed that walls of building were thick enough to block any transmission that passes through them. In that case, two nodes located on opposite sides of one or more walls would not be able to communicate with each other.…”
Section: E Signal Propagation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently though, various mobility models have been proposed which attempt to better capture mobility traces than RWM. These mobility models range from Obstacle Mobility Model [2] to City Section Mobility models (see the survey [3]). …”
Section: Introductionmentioning
confidence: 99%